2020
DOI: 10.3390/ijerph17186722
|View full text |Cite
|
Sign up to set email alerts
|

The Outrage Effect of Personal Stake, Familiarity, Effects on Children, and Fairness on Climate Change Risk Perception Moderated by Political Orientation

Abstract: Outrage factors are perceived characteristics of risk that provoke emotional responses and influence risk perception. Although several studies examined how multiple influences affect climate change risk perception, outrage factors have not been comprehensively assessed in the context of climate change risk perception. Using an online survey in South Korea (n = 592), we investigated outrage factors associated with climate change risk perception and whether political orientation moderates these outrage effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Indeed, multiple studies provide empirical findings that signify the association between risk perception and political orientation. Here, the specific risks that were examined included climate change (Carvalho & Burgess, 2005; Dunlap & McCright, 2008; Hamilton, 2011; Hindman, 2009; Krosnick, Holbrook, & Visser, 2000; McCright & Dunlap, 2011; Wood & Vedlitz, 2007; You & Ju, 2020), local weather change (Shao & Goidel, 2016), heat wave (Cutler et al., 2018), and fine dust (Ju & You, 2020). The proportion of Democrats in the United States that supported the concept of global warming, for example, increased from 47% in 1998 to 75% in 2008, whereas the percentage of Republicans decreased from 46% to 41% during the same period, signifying that climate change risk perception varied according to party affiliation (Dunlap & McCright, 2008).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, multiple studies provide empirical findings that signify the association between risk perception and political orientation. Here, the specific risks that were examined included climate change (Carvalho & Burgess, 2005; Dunlap & McCright, 2008; Hamilton, 2011; Hindman, 2009; Krosnick, Holbrook, & Visser, 2000; McCright & Dunlap, 2011; Wood & Vedlitz, 2007; You & Ju, 2020), local weather change (Shao & Goidel, 2016), heat wave (Cutler et al., 2018), and fine dust (Ju & You, 2020). The proportion of Democrats in the United States that supported the concept of global warming, for example, increased from 47% in 1998 to 75% in 2008, whereas the percentage of Republicans decreased from 46% to 41% during the same period, signifying that climate change risk perception varied according to party affiliation (Dunlap & McCright, 2008).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Outrage factors in particular were regarded as qualitative risk characteristics that elicit emotive responses of the public to a risk that then lead to heightened risk perception (Sandman, 1993). These emotion‐eliciting factors were found to be influential in public responses concerning various types of risk, such as food risk (You & Ju, 2017; You et al., 2019; Heyes, 2012), climate change (You & Ju, 2020), and fine dust (Ju & You, 2020). In this study we controlled for outrage factors, and therefore could also examine whether political orientation moderates possible outrage effects on infectious disease risk perception, via another research question: RQ2b: Does political orientation moderate the possible influence of outrage factors on risk perception and coping behaviors associated with COVID‐19? …”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Wu and Lu (2013) further suggested that, among four dimensions of environmental concern (i.e., the source of knowledge, familiarity with environmental knowledge, awareness of environmental pollution, and attitudes to environmental issues), familiarity with environmental knowledge demonstrated the greatest positive relationship with recycling behavior. The positive relationships between the risk perception of climate change, which was highly related to familiarity with climate change (You & Ju, 2020), and pro-environmental behaviors (Bradley et al, 2020) also suggested that familiarity with climate change would be positively related to pro-environmental behaviors.…”
Section: Intergenerational Transmission Of Pro-environmental Behaviorsmentioning
confidence: 99%
“…Morss et al (2020) No insights into role of affective response in risk communication. You and Ju (2020) No insights into role of affective response in risk communication.…”
Section: Ekholm (2020)mentioning
confidence: 99%